Role of stress and physical activity on primary dysmenorrhea: A cross-sectional study - Triwahyuningsih, Ria Y.; Rahfiludin, M. Zen; Sulistiyani, Sulistiyani; Widjanarko, Bagoes (Narra Sains Indonesia, 2024)
The initial physiological change in adolescent girls is the onset of menstruation. The most prevalent challenge they face regarding menstruation is primary dysmenorrhea, characterized by persistent or intermittent pelvic pain in the lower abdomen. The aim of this study was to investigate the influences of stress levels and physical activities on primary dysmenorrhea. A cross-sectional was conducted in Cirebon, Indonesia, in 2023 included young women who had never given birth (nullipara), aged 17–25 years old, had menstruated, and had no history of smoking and alcohol. The data were collected using a set of questionnaires consisting of the Numeric Rating Scale (NRS) to determine primary dysmenorrhea pain, the Depression Anxiety Stress Scales 42 (DASS 42) to determine the level of stress and the International Physical Activity Questionnaire (IPAQ) to determine physical activity. Pearson's correlation test was used to assess the correlation between the variables (stress levels, physical activity, and dysmenorrhea). A total of 150 young women were included in the study. Moderate stress levels (23.3%) and high physical activity (90.7%) were the most prevalent categories observed among studied participants. Approximately 42% of them experienced mild dysmenorrhea pain. Our analysis indicated that stress levels and physical activities had strong positive correlations with dysmenorrhea pain levels, with r=0.782 and r=0.748, respectively, with both had p<0.001. This highlights that controlling stress could be beneficial in preventing dysmenorrhea pain among young women.